Serat dan Status Gizi Kaitannya dengan Tekanan Darah pada Pasien Hipertensi Rawat Inap di Rumah Sakit Umum Daerah Tugurejo Semarang - Fitria Nur Kholifah; Sufiati Bintanah; Erma Handarsari (Jurnal Gizi, 2016)
Hypertension is called the silent killer is a disease prevalent in society is characterized by sistolic blood pressure ? 140 mmHg and diastolic ? 90 mm Hg. The fiber is called "roughage," helpskeep your body stay organized. Low fiber intake ? 8.8 g / day increased C-Reactive Protein (CRP) 4kali higher in adults with two or three risk of disease (obesity, hypertension, diabetes). This study determine the relationship of dietary fiber intake and nutritional status with blood pressure in hypertensive patients hospitalized in the Hospital Tugurejo Semarang. Methods: reaserch explanatory research with cross sectional approach. The population of all patients presenting to the hospital in May 2014, samples taken as many as 26 people with purposive sampling technique.Univariate analysis performed to present the frequency distribution table. Bivariate analysis begins with Shapiro-Wilks normality test and continued with correlation of Rank-Spearman. Most (34.6%) samples were aged 51-60 years, and most (65.4%) were female, most ( 69.2%) intake of fiber <20 grams,. For fiber intake of the average patient lack of demand (20 grams), the majority (46.2%) had a better nutritional status with BMI> 25 experienced by as many as 18 respondents (69.2%), the majority (61.5% ) had a systolic blood pressure of 140-159 mmHg, most (46.2%) had blood pressure of 90-99 mmHg. Statistical analysis showed that there was a negative association between dietary fiber intake with systolic blood pressure (p = 0.001 <0.005), there was no association between dietary fiber intake with diastolic blood pressure (p = 0.374> 0.05). ), There is a relationship between nutritional status and systolic blood pressure (p = 0.033 <0.05). ), And there is no relationship between nutritional status and diastolic blood pressure (p = 0.842> 0.05). Lower fiber intake will increase systolic blood pressure. The nutritional status related to blood pressure, the more the higher the nutritional status of blood pressure. Diastolic blood pressurewas not associated with the level of konsusmi fiber and nutritional status.Keywords: Fiber intake, nutritional status, Blood Pressure, Hypertension Patients.